Postoperative Neurological Monitoring and Care Stratification in Adult Patients After Craniotomy: A Systematic Literature Review - Imanuella Imanuella; Fayza Asyahlaa Rihastara; Fiza Paluphi Andita Nugroho; Nurur Rachman Machmudy; Muhammad Muttaqien; Ika Yuni Widyawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
The postoperative period following craniotomy is a critical phase because patients are at risk for early neurological deterioration, the need for escalation of care, delirium, delayed awakening, and other complications that can impact safety and clinical outcomes. An appropriate approach to neurological monitoring, including the selection of the care unit and stratification of observation intensity, is a crucial issue in modern neurosurgical practice. Synthesizes current scientific evidence regarding postoperative neurological monitoring and care stratification in adult patients after craniotomy, specifically regarding the safety of non-intensive care unit (non-ICU) care, the use of prediction scores, and postoperative clinical outcomes. This review used a systematic literature review design following the PRISMA 2020 principles and has been registered with PROSPERO (CRD420261350040). Searches were conducted in PubMed, Scopus, Web of Science, SAGE, and Springer Nature for articles published between 2020 and 2026. Methodological quality was assessed using the Joanna Briggs Institute Critical Appraisal Tools according to study design. Due to the heterogeneity of designs, interventions, and outcomes, the synthesis was conducted narratively and thematically. Of the initial 534 articles, 18 studies met the inclusion criteria. Four studies were of high quality and fourteen studies were of moderate quality. Three main themes were identified: (1) non-ICU monitoring pathways in selected patients can be safe when supported by structured neurological observation; (2) prediction scores and risk stratification help adjust monitoring intensity; and (3) structured postoperative pathways, including same-day discharge in selected patients, have the potential to reduce length of stay, costs, and ICU use without showing significant safety signals. Available evidence suggests that structured, risk-based postoperative neurological monitoring supported by strong nursing competencies has the potential to improve resource efficiency without compromising patient safety. However, the evidence remains largely based on observational studies.